RideCycle: reduce reuse recycle / Fahmeeda Nadzirah Zuren Effendy - Effendy, Fahmeeda Nadzirah Zuren (Faculty of Art and Design, 2020)
Human life is the world's source of sustenance. One of the efforts that have been made in recycling project is to take care of the environment and also to cultivate a recycling practice among the community, thereby increasing the rate of recycling percentage in Malaysia by introducing new recycling services "RideCycle'.